An examination of victimization trajectories among a sample of South Korean adolescents: risk and protective factors - Lee, Yeungjeom (Crime & delinquency, 2017)
Although a large body of criminological studies have examined trajectories of offending, only a handful of studies have attempted to explore victimization trajectories. The purpose of the current study is to use group-based modeling to explore victimization trajectories among Korean youth and to identify factors that protect and jeopardize victims over the life course. The present study uses data from five waves of Korean Youth Panel Survey (KYPS). Results show three distinct victimization trajectories and identify several risk and protective factors of repeat victimization. Suggestions for future research are discussed.